Perceptions and practices of clinicians on the autonomy of the surgical patient during the process of taking informed consent. Santo Domingo de los Tsáchilas, Ecuador - Gonzaga Troya, Luis Francisco; Díaz-Pérez, Anderson (Acta Bioethica, 2023)
The way in which the clinician perceives the patient and his knowledge about informed consent (IC) are reflected in practices of respect for the patient, in relation to their autonomy and privacy from an ethical, deontological and legal framework. Objective. Analyze the perceptions and practices by surgeons in relation to the respect of the autonomy of the patient during the process of taking the IC in a hospital in the city of de Santo Domingo de los Tsáchilas / Ecuador. Methodology. Cualitattivo. The sample was by saturation applying a semi-structured interview. The data were analyzed using the Atlas Ti 8.0 ® program using structured category tracking. Result. Most doctors take consent as a legal and mandatory document, for fear of sanctioning processes. In addition, they usually delegate their responsibility to other professionals ignoring structural and ethical components of taking informed consent. Conclusion. It is evident that the lack of knowledge about IQ leads to perceptions, and therefore, to practices that violate autonomy and confidentiality, in addition to the respect of receiving information from the clinician who performed the intervention.